Estratégias e políticas de conversão da zona econômica especial Luanda-Bengo, Viana KM 27, Luanda, Angola, em parque industrial ecológico - Vissuma, Belarmino Gouveia (2013)
The adverse impacts of anthropic actions on the environment have been noted from the moment that human activities acquired an organized form. Industrial activities have been identified as the engine of economic growth and expansion of wealth. At the same time, these activities require huge amounts of natural resources and generate waste and emissions that the surrounding ecosystems are unable to contain. The concern of environmental degradation has led to varied proposals for improving the sustainability of industrial activity. One of these proposals, arising from industrial ecology, is Eco-industrial Parks. Eco-industrial Parks aim at designing sustainable industrial systems, in which waste from one industry is reused in other industries found in geographical proximity, providing economic, environmental and social benefits. This dissertation aims to propose strategies and policies needed to convert the Industrial Park km 27 of the Special Economic Zone Luanda-Bengo, Angola, into an Ecological Industrial Park, as a proposal to provide the country with performance instruments for the promotion of sustainable development. To develop the proposed Industrial Symbiosis, a field visit to the park and data and information surveys were made of the industrial units operating in the SEZ Luanda-Bengo, concerning production, waste generated and its destination, as well as conditions in the area. Some limitations were noted in this survey along with opportunities for the conversion of the SEZ into an eco-industrial park. The main opportunities are the diverse industries and the proximity between them, the existence of a wastewater treatment plant as a service offered at no cost to all units installed there and the existence of tax incentives for exploration. One limitation is the lack of legislation concerning waste disposal and treatment. This work proposes a methodology for converting probable scenarios, according to the methodology proposed by Doyle et al (1996). The first scenario describes current activities of the businesses and the existing opportunities and conditions in relation, in the second scenario measures are proposed to prevent pollution in regards to the activities described in the first scenario, the third scenario provides the proposed industrial symbiosis, a symbiosis with the new members of the park is proposed in the fourth scenario, and in the fifth scenario is the inclusion of communities surrounding the proposed symbiosis. This study demonstrated that the creation and strict implementation of environmental legislation, training on actions to prevent pollution and the creation of incentives for companies to cooperate are essential factors for conversion of the Special Economic Zone Luanda-Bengo into an eco-industrial park.